Rasamritam: A Comprehensive Study on Rasausadhies and Their Therapeutic Guidelines (International Journal of Ayurveda and Pharma Research, 2024)
Ras Shastra emerged in the Ayurveda medicinal tradition in addition to the use of minerals and metals. Numerous faiths, groups, and customs have influenced the evolution of Ras Shastra. As a result of this contribution, many books related to Rasa Shastra came into circulation. This tradition started from the medieval period and has persisted to the present time. Through Rasamritm, Acharya has actually presented the essence of the subject of Ras Shastra in this book in such a way that this book has actually become the nectar for the subject. This book contains the effective practical portion of the entire subject. It consist nine chapters and nine appendices in total. The text contains of both the theoretical and practical aspects. Rasa yoga are mentioned at the end of every chapter. Particularly, the ninth chapter only consist of Rasa yoga. Some of those are the new formulations, and some have been altered from the original text in some way. Few of the Unani formulations are also includes. The author also discusses possible chemical reactions and alterations while making Rasaushadhies. This article has been reviewed in order to gather all of the Ras-yogas mentioned in this text at one place. From this review, one can easily find the formulation with all the necessary information.